2016
DOI: 10.1371/journal.pone.0166400
|View full text |Cite|
|
Sign up to set email alerts
|

Palmitoylated APP Forms Dimers, Cleaved by BACE1

Abstract: A major rate-limiting step for Aβ generation and deposition in Alzheimer’s disease brains is BACE1-mediated cleavage (β-cleavage) of the amyloid precursor protein (APP). We previously reported that APP undergoes palmitoylation at two cysteine residues (Cys186 and Cys187) in the E1-ectodomain. 8–10% of total APP is palmitoylated in vitro and in vivo. Palmitoylated APP (palAPP) shows greater preference for β-cleavage than total APP in detergent resistant lipid rafts. Protein palmitoylation is known to promote pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…This process involves several enzymes, including BACE1 ( β -site A PP c leaving e nzyme) and β- and γ-secretases. Bhattacharyya et al (2013 , 2016 ) reported that two N-terminal cysteine residues of APP (Cys186 and Cys187) undergo S-PALM. S-PALM APP is enriched in membrane lipid rafts and forms dimers, leading to elevations of BACE1-mediated cleavage of the protein ( Bhattacharyya et al, 2013 ).…”
Section: Palmitoylation and Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves several enzymes, including BACE1 ( β -site A PP c leaving e nzyme) and β- and γ-secretases. Bhattacharyya et al (2013 , 2016 ) reported that two N-terminal cysteine residues of APP (Cys186 and Cys187) undergo S-PALM. S-PALM APP is enriched in membrane lipid rafts and forms dimers, leading to elevations of BACE1-mediated cleavage of the protein ( Bhattacharyya et al, 2013 ).…”
Section: Palmitoylation and Neurological Diseasesmentioning
confidence: 99%
“…The PULSE-CHASE labeling method has been successfully applied for decades. This method allows determination of the half-lives of the S-PALM of various proteins, including ankyrin ( Staufenbiel, 1987 ), Gαi ( Degtyarev et al, 1994 ), α2A-adrenergic receptors ( Kennedy and Limbird, 1994 ), HTT ( Sanders and Hayden, 2015 ), BACE1 ( Bhattacharyya et al, 2016 ), H-Ras ( Baker et al, 2003 ), and N-Ras ( Magee et al, 1987 ). In this approach, cells are exposed to radioactively labeled palmitate for a short period of time (i.e., the PULSE phase), followed by a phase in which cells are incubated with unlabeled (non-radioactive) palmitate (i.e., the CHASE phase).…”
Section: Metabolic Labelingmentioning
confidence: 99%
“…Earlier reports showed that transmembrane TNF is palmitoylated which regulates its affinity to TNF-R1 [68, 69]. FasL and also the putative DR6 ligand APP require palmitoylation for their biological function [7072]. We ruled out a possible role for endogenous TNF on TNF-R1 palmitoylation by co-culture with TNF targeting Fab.…”
Section: Discussionmentioning
confidence: 96%
“…However, these APP palmitoylation sites are somewhat unusual in that they are localized to the extracellular (luminal) domain, rather than in the cytoplasmic domain of the protein where most palmitoylation sites of transmembrane proteins are found (99). Palmitoylation has been suggested to regulate APP association with DRMs and processing in rafts, as well as its dimerization (99,100). Importantly however, the C99 domain of APP lacks any cysteines and can therefore cannot undergo palmitoylation, ruling out the possibility that this form of posttranslational modification determines whether C99 itself associates with rafts.…”
Section: Discussionmentioning
confidence: 99%